6 Hz transcranial alternating current stimulation of mPFC improves sustained attention and modulates alpha phase synchronization and power in dorsal attention network. Issue 1 (2nd January 2021) - Rostami, Reza; Kazemi, Reza; Mozaffarinejad, Farzaneh; Nasiri, Zahra; Rostami, Maryam; L.Hadipour, Abed; Sadeghihassanabadi, Fatemeh
ABSTRACT: Transcranial alternating current stimulation (tACS) is a noninvasive brain stimulation tool appropriate to modulate cortical oscillations and activity via the application of weak currents. The major goal of this study was to investigate the effects of medial Prefrontal Cortex (mPFC) stimulation on sustained attention task performance measured by Rapid Visual Information Processing (RVIP) task and the brain networks assumed to be critical to sustained attention. mPFC has been shown to be involved in sustained attention performance and as a main hub in default mode network (DMN). mPFC activity modulation via theta tACS was implemented in this study. This was a single blind study with 21 participants receiving active and sham stimulation with the electrodes on FPz and the Inion. tACS was able to impact different RVIP measures (total hits, A' (sensitivity to target), total correct rejection, etc.). Relative power spectrum density (PSD) analysis yielded significant increases in theta frequency mostly in the fronto-central regions after active tACS and current source density (CSD) analysis yielded significant power modulations in theta frequency band in post-central gyrus. Furthermore, phase locking value (PLV) analysis showed that there were significant changes in cortical connections in the Dorsal Attention Network (DAN) in alpha frequency band. This study showed that theta frequency tACS over mPFC, was able to produce significant modulations in an RVIP task and its associated brain networks in healthy participants.